(untitled) (Revista Iberoamericana de Estudios Municipales, 2024)
This article analyzes the territorialization of public policies carried out by the Frente Amplio (FA) governments in Uruguay. With this objective, we describe the capacity for action and decisionmaking that local units of the central level have had in the territory. We argue that, despite the decentralizing discourse, the decision-making capacity of these units is scarce, with functions remaining in the hands of central actors. At a conceptual level, we present a typology of power allocation and distribution between central and peripheral actors in the definition and implementation of public policies, creating an index that measures the autonomy of local actors. To provide evidence for our argument, the index is applied to 159 sectoral programs.